Johnson & Johnson position in the pharmaceutical industry competitive landscape - Gonçalves, Henrique Miguel Da Rocha (2022)
This work project “Johnson & Johnson Place in the Pharmaceutical IndustryCompetitive Landscape” analyses Johnson & Johnson business within the pharmaceutical industry. Given the demand for JNJ products and the growth in revenues brought with COVID-19 due to the Janssen vaccine sales, we estimate a sales growth of 11.4% compared to last year. We will analyze the COVID-19 pandemic current and possible future implications for the industry and the company and compare it with other pharmaceutical companies which are COVID-19 vaccine producers. We will also investigate JNJ most relevant mergers and acquisitions as well as to examine the pharmaceutical industry and the current and future evolution of microeconomic indicators both in the US and the rest of the world. Our valuation of Johnson & Johnson yields a price target of 197.57$ which results in a return of 16.03% and therefore a BUY recommendation